High-dose dual therapy is effective as first-line treatment for Helicobacter pylori infection - Öztürk, Kadir; Kurt, Ömer; Çelebi, Gürkan; Şarlak, Hakan; Karakaya, Muhammed Fatih; Demirci, Hakan; Kılınç, Ali; Uygun, Ahmet (Turkish Journal of Gastroenterology, 2020)
Background/Aims: Although many regimens, including quadruple, sequential, and concomitant treatment, are used and recommended as first-line or rescue therapies for Helicobacter pylori infection, eradication rates are still below 90% in intention-to-treat analyses. Treatment protocols with substantially high eradication rates and low antibiotic resistance are needed. In this study, we investigated the efficacy of high-dose dual therapy as first-line treatment in a Turkish population.Materials and Methods: All patients underwent upper gastrointestinal endoscopy for the initial H. pylori status because of dyspeptic symptoms. All patients received a 14-day, high-dose dual therapy comprising rabeprazole (20 mg t.i.d.) and amoxicillin (1 g t.i.d.) for H. pylori eradication. H. pylori stool antigen tests of eradication were administered to all participants at least 4 weeks after the completion of the treatment.Results: The high-dose dual therapy demonstrated a 91.3% rate of successful eradication of H. pylori infection. Per-protocol success was 94.4% among female patients (n=51) and 89.6% among male patients (n=86); in terms of gender, the differences were not significant (p=0.310). No side effects were observed during the study in any patient. Six other patients did not take adequate doses of the treatment protocol.Conclusion: High-dose dual therapy with rabeprazole and amoxicillin was highly effective and well tolerated as a first-line therapy for H. pylori eradication.